Topics in dental biochemistry - Levine, Martin; SpringerLink (Online service). (Berlin London Springer, 2011)
Over the last 20 years, biochemistry and molecular biology have undergone a revolution that has affected our understanding of the oral cavity. Topics in Dental Biochemistry is primarily designed for students of dentistry who need to relate biochemistry and molecular biology to dentally related topics in physiology, nutrition, anatomy, histology, microbiology, and immunology. The book will also be of value for dental professionals, scientists, and practitioners of medicine who are interested in hard and soft tissue structure and disease. It provides the necessary basic scientific background for a clearer understanding of bone, tooth, saliva, and surrounding soft tissue research and also for an appreciation of how dental caries and periodontal disease might be better diagnosed and controlled in the future. Dentistry was developed to treat dental caries, but since the early 20th century it has increasingly been treating periodontal, traumatic and genetic diseases affecting tooth structure and attachment. Fluoridation is discussed at length. Other methods for controlling dental caries and new or suggested methods for controlling oral hygiene and periodontal disease are also discussed.
Necessary basics: elements, isotopes, ions, chemical reactions, energy metabolism and bacterial structures -- Photosynthesis and sucrose production -- The connective tissue extracellular matrix and its major components -- Fibrillar and non-fibrillar collagens & its integrin attachments -- Basal laminas and epithelia -- Elastic fibers and proteoglycans -- Collagen synthesis, genetic diseases and scurvy -- The zincins: collagen fiber processing and degradation -- Biological mineralization -- Bone remodeling and calcium metabolism -- Blood Coagulation -- Saliva -- Chronic Periodontitis -- Aggressive Periodontitis -- Dental caries -- Fluoride.
Electronic reproduction.
Keywords: Biochemistry; Mouth -- Diseases; Electronic books